Os dilemas e as proposições da educação ambiental na Transamazônica (BR-230): do atendimento às normas para o licenciamento ao encontro das expectativas das comunidades da rodovia - CORRÊA, Edisa Assunção (Universidade Federal do Pará, 2015)
This paper will present a study conducted in rural communities in the municipality of Altamira in Para State aims to analyze the results of the Environmental Education actions implemented by the BR-230 program by the municipality of Altamira PEA - BP in 2010 to 2011 contributed to the integration of the practice of environmental education in communities, as well as for the formation of an environmental conscience. The theoretical and methodological framework bolstered in qualitative based on a perspective of critical environmental education; this included the analysis of documents related to the program, as well as documents from city hall and literature. The survey was conducted using questionnaires containing open questions directed to the facilitators of the program, interns and residents with some of the communities in question. Among the authors who helped in understanding the context studied include: Frederick Loureiro ( 2004, 2005, 2007, 2009 2012), Marilena Loureiro (2007 ), Violet Loureiro (2009, 2011), Bertha Becker (2009, 2011), among others. This research allowed us to understand the linkages among environmental education thought to the region from the resumption of the paving of BR -230, but known to transamazônica. This new scenario is presented from multiple perspectives by directly affected by this highway configured as a favorable place to acercas discussions of environmental impacts communities.